THE DIGNITY OF THE INDIVIDUAL IN THE CONTEXT OF THE APPLICATION OF SANCTIONS (EUROPEAN AND ASIAN LAW REVIEW, 2024)
In the article, the author analyzes the consequences of the application of certain types of sanctions. The author notes that unilateral termination of concluded contracts and refusal to conclude new contracts with individuals (due to their discrimination on the territory of residence, nationality, citizenship) can cause moral harm, expressed in humiliation of human dignity caused by negative experiences and emotions of a person, and not in underestimation of self-esteem. At the same time, the author points out that in the conditions of the application of sanctions, the very concept of "dignity", and methods and measures of its protection need further theoretical understanding.
Keywords: honor; dignity; protection; moral feelings; moral harm